2018
DOI: 10.5812/ijcm.61383
|View full text |Cite
|
Sign up to set email alerts
|

The Radioprotective Effects of Nano-Curcumin Against Genotoxicity Induced by Iodine-131 in Patients with Differentiated Thyroid Carcinoma (DTC) by Micronucleus Assay

Abstract: Background: Breast cancer is the most common cancer among women worldwide. Objectives: Regarding the effect of delay on survival in patients with breast cancer and the high incidence of delayed presentation in these patients in Iran, we decided to study the factors affecting delay in seeking treatment in patient with breast cancer in Kerman, South-east of Iran. Methods: In this cross sectional study, 80 cases (with delay time less than 3 months) and 80 controls (patients with delay time more than 3 months) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…224,246,247 It also reduced DNA damage and micronuclei formation in lymphocytes of thyroid cancer patients. 228 Moreover, the antidiabetic properties of nanocurcumin were attributed their capacity in reducing FBG, glycated Hb, insulin, hs-CRP, TC, TAC, TN, LDL-C, VLDL-C, TC/HDL-C, MDA, and augmented insulin sensitivity, TAC, peroxisome proliferator-activated receptor gamma (PPARγ), LDLR, and GSH levels in T2D patients. 248−251 It also suppressed neuropathy, depression, and anxiety in T2Dassociated peripheral neuropathy patients.…”
Section: Methodsmentioning
confidence: 99%
“…224,246,247 It also reduced DNA damage and micronuclei formation in lymphocytes of thyroid cancer patients. 228 Moreover, the antidiabetic properties of nanocurcumin were attributed their capacity in reducing FBG, glycated Hb, insulin, hs-CRP, TC, TAC, TN, LDL-C, VLDL-C, TC/HDL-C, MDA, and augmented insulin sensitivity, TAC, peroxisome proliferator-activated receptor gamma (PPARγ), LDLR, and GSH levels in T2D patients. 248−251 It also suppressed neuropathy, depression, and anxiety in T2Dassociated peripheral neuropathy patients.…”
Section: Methodsmentioning
confidence: 99%
“…Radiation therapy triggers different cellular signaling pathways that lead to the activation of proinflammatory cytokines and thus the development of inflammatory responses 111 . One study found that the administration of 160 mg/day of nano‐curcumin to patients with differentiated thyroid cancer could prevent genetic damage in peripheral blood lymphocytes by radiation.…”
Section: Effect Of Nano‐curcumin On Cancer Patientsmentioning
confidence: 99%
“…Radiation therapy triggers different cellular signaling pathways that lead to the activation of proinflammatory cytokines and thus the development of inflammatory responses. 111 One study found that the administration of 160 mg/day of nano-curcumin to patients with differentiated thyroid cancer could prevent genetic damage in peripheral blood lymphocytes by radiation. In this study, administration of nano-curcumin from 3 days before up to 7 days after radiation therapy prevented the increase of peripheral lymphocyte micronuclei that cause significant genotoxic damage.…”
Section: Effect Of Nano-curcumin On Cancer Patientsmentioning
confidence: 99%
“…The vitamin E and curcumin defense impact T4-induced oxidative stress in rats' renal cortex was reported by modulation of antioxidant enzymes and oxidative stress parameters (35). Orally administration of curcumin (160 mg/day) 3 days before and 7 days after I-131 therapy inhibited oxidative and genotoxic damage (66).…”
Section: Antioxidant Actionmentioning
confidence: 99%